Advantages and problems of electric microwave processing plants with hybrid working chambers. Issue 1 (2nd January 2023) - Tuhvatullin, Midhat; Arkhangelsky, Yuri; Aipov, Rustam; Akhmetshin, Arthur; Atnagulov, Dinar
Abstract: This article presents information about the design and purpose of microwave processing plants of thermal, non-thermal microwave modification and microwave processing plants with hybrid working chambers that have not yet been widely used. This article also presents and justifies advantages of electric microwave processing plants with hybrid chambers over electric microwave processing plants used for thermal treatment of dielectric materials and non-thermal treatment of polymer materials. These advantages give reason to talk about the expediency of widespread use of electric microwave processing plants with hybrid working chambers in industry and agriculture. This article formulates and justifies the problems of electric microwave processing plants with hybrid working chambers. Thus, high prices for microwave generators reduce the profitability of the plant. The research is being carried out within the framework of a grant as subsidies in science from the budget of the Republic of Bashkortostan for the state support of young scientists – candidates of sciences (the competition code is REC–Federal and State Management – 2022).